A produção textual dos formandos de letras de uma instituição pública do estado do Paraná: um estudo sobre a coerência - Ranckel, Michelle (2011)
The perspective that if has in relation to the literal production of university students is of that, after every year of studies of Portuguese Language, them they have incorporated at least the rules less complex, as referring to the cohesion and the coherence and the too much normative questions on accent, orthography, punctuation and agreement. The subject is preoccupying and also reason to develop an inquiry. Thus, this work of research objectified to inquire as they write students of the course of Letters. It was opted to the inquiry of the found literal incoherence in the period of training reports, elaborated for the academics of the course of Letters, as final work for disciplines Methodology of Portuguese Education, in the years of 2006, 2007 and 2008, of the State College of Philosophy, Sciences and Letters of Union of the Victory. In this work the productions of the academics had been analyzed in order to characterize the professional profile of the area of Letters in what it refers to the examination of the literal incoherence, specifically, of the repetition, progression, notcontradiction and of the relation of the coherence mechanisms. Of this form, to investigate the grammatical aspects of the texts of the academics meant to identify the profile of the professional of Letters in accord with its capacity to act with ability and ability the proper object of its area, the language. The inquiry selected 34 reports, elaborated for the academics. The general objective of the research is: to investigate the literal coherence of the written productions of the reports of period of training elaborated by the academics. The specific objectives: to verify the literal coherence of the reports in its dimension of repetition; to desvelar the coherence of the writings in its dimension of the subject progression; to analyze the literal coherence in its dimension of not-contradiction; to detect the coherence of the texts written for the trainees in its dimension of relation. The used methodology was to the content analysis, in its modality of thematic analysis to verify if the mechanisms really they are used and with that frequency. After accomplishment of the research we can confirm that it has lack of ability of the pupils in the production of the report and this is each more preoccupying time if we will be to consider that must mainly be responsibility of the college and of the course of Letters the development of the abilities and abilities which are proposals in the Project Pedagogical Politician of the IES in study. The observed citizens must display texts with “start, way and end”, to transfer an idea and if to want to relate them goal rule of Charolles (1978, apud GALVES, 1988). Being thus, it was possible to conclude that goal rule of the Repetition and of the Progression, they appear in the productions of the academics, in contrast of the relation and not the contradiction. We believe that the future professors of maternal language know the importance of the construction of a coherent text and, fitting and lacking to the university to offer subsidies to its pupils so that they can have more contact with the correction of its productions.